2009
DOI: 10.3748/wjg.15.3555
|View full text |Cite
|
Sign up to set email alerts
|

Generalized megaviscera of lupus: Refractory intestinal pseudo-obstruction, ureterohydronephrosis and megacholedochus

Abstract: Dilated dysfunction involving multiple visceral organs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 11 publications
2
37
0
Order By: Relevance
“…A possible explanation for the poor response to therapy in this patient was the delay in commencement of immunosuppressants, which resulted in non-resolution of symptoms in a previous case report. 14 In 12 of the 18 patients reviewed by Mok et al and isolated case reports, 14,15 associated bilateral ureterohydronephrosis and megacholedochus were noted, which was absent in our patient. The classical histological feature of gastroparesis is intestinal leiomyocyte damage, 13 thus the normal gastric mucosal biopsy in this patient does not assist with the differential.…”
Section: Discussionsupporting
confidence: 48%
“…A possible explanation for the poor response to therapy in this patient was the delay in commencement of immunosuppressants, which resulted in non-resolution of symptoms in a previous case report. 14 In 12 of the 18 patients reviewed by Mok et al and isolated case reports, 14,15 associated bilateral ureterohydronephrosis and megacholedochus were noted, which was absent in our patient. The classical histological feature of gastroparesis is intestinal leiomyocyte damage, 13 thus the normal gastric mucosal biopsy in this patient does not assist with the differential.…”
Section: Discussionsupporting
confidence: 48%
“…However, restoration of bowel function, resolution of symptoms and prevention of complications like recurrent intra-peritoneal adhesions and irreparable tissue damage can only be achieved if there is early recognition and timely initiation of treatment. 3,10 Early detection also avoids unnecessary invasive procedures and other surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This rare triad of gastrointestinal, genitourinary, and hepatobiliary hollow viscera dilatation has been described in lupus only twice previously but never been distinguished in its early stage [4,5]. The pathophysiology of IPO secondary to SLE remains unclear [3], though several hypotheses have been proposed [1,4,[6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of IPO secondary to SLE remains unclear [3], though several hypotheses have been proposed [1,4,[6][7][8]. The high association between IPO and ureterohydronephrosis suggests a smooth muscle dysmotility due to a primary neuropathy or myopathy, or secondary to either an immune complexmediated vasculitis or common autoantibody against the smooth muscles [4] Generalized vasculitis involving inXammatory Wbrinoid deposits or smooth muscle muscularis propria dysmotility may also aVect the smooth muscle of the intestine and lead to small bowel obstruction. MoK MY et al [1] reported six cases and reviewed 12 cases presented with IPO in SLE, most of whom were Asia descent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation